DETERMINAN IMUNISASI DASAR PADA BALITA DI INDONESIA: STUDI PEDESAAN - Syahfitri, Rizky Indah; Ismah, Zata; Susanti, Nofi (Poltekkes Kemenkes Bandung, 2024)
According to the results of the Riskesdas report, basic immunization coverage in Indonesia in 2017 only reached 59.4% and 57.9% in 2018. This figure is still far from the strategic plan target set by the Ministry of Health in 2019, namely 93%. The research aimed to analyze the factors that influence the incomplete basic immunization status of children in rural areas, Indonesia. This research is a quantitative research designCross Sectional. The data used is secondary data originating from the 2017 Indonesian Demographic and Health Survey (SDKI). The sampling technique usedtotal sampling amounting to 3,111 children under five. Based on the results of this study, it can be concluded that the determinants of incomplete basic immunization for toddlers in rural areas of Indonesia are less than 3 antenatal visits, delivery not in a health facility, distance to health facilities is a big problem, mother's age is less than 25 years, father's education is low, and the order of the 3rd child, etc. The chance of children not having complete basic immunization for toddlers in rural areas of Indonesia if all risk factors are present is 86%. The most dominant risk factor influencing incomplete basic immunization status is fewer than 3 antenatal visits. It is recommended that health workers prioritize health promotion programs regarding the benefits of antenatal visits by approaching community leaders, especially midwives.